Treatment of migraine attacks and prevention of migraine: Guidelines by the German Migraine and Headache Society and the German Society of Neurology. Issue 1 (30th January 2019) - Diener, Hans-Christoph; Holle-Lee, Dagny; Nägel, Steffen; Dresler, Thomas; Gaul, Charly; Göbel, Hartmut; Heinze-Kuhn, Katja; Jürgens, Tim; Kropp, Peter; Meyer, Bianca; May, Arne; Schulte, Laura; et al.
In collaboration with some of the leading headache centres in Germany, Switzerland and Austria, we have established new guidelines for the treatment of migraine attacks and the prevention of migraine. A thorough literature research of the last 10 years has been the basis of the current recommendations. At the beginning, we present therapeutic novelties, followed by a summary of all recommendations. After an introduction, we cover topics like drug therapy and practical experience, non-effective medication, migraine prevention, interventional methods, non-medicational and psychological methods for prevention and therapies without proof of efficacy.